The Relationship Between Parental Accommodation and Sleep-Related Problems in Children with Anxiety. Issue 2 (February 2021) - Chevalier, Lydia L.; O'Connor, Erin E.; Holly, Lindsay E.; Langer, David A.; Pincus, Donna B.
ABSTRACT: Objective: Sleep-related problems, defined as sleep patterns atypical for the child's developmental stage, are common in children with elevated anxiety symptoms and linked to significant mental and physical health consequences. Despite the consequences of sleep-related problems, it remains unclear how these problems are initiated and maintained in children with elevated anxiety symptoms. The current study examines the relationship between sleep-related problems and parental accommodation (e.g., co-sleeping) to determine whether higher levels of accommodation are associated with more frequent sleep-related problems in a sample of children with elevated anxiety symptoms. Methods: Participants were 122 children aged 8 to 17 years old (M = 11.97, SD = 2.68; 57% female) and their parents who presented to a university-based anxiety specialty clinic for assessment and treatment. Children completed the Multidimensional Anxiety Scale for Children, and their parents completed the Children's Sleep Habits Questionnaire and Family Accommodation Checklist and Interference Scale. Multiple regression analyses were performed to examine variance in sleep-related problems explained by parental accommodation. Results: Parental accommodation accounted for a significant amount of variance in sleep-related problems over and above child anxiety and age for both mother report (19%) and father report (15%). When individual accommodation items were examined, parental sleep accommodations (e.g., slept in my child's bed) and nonsleep accommodations (e.g., came home early) were significant predictors for mother-reported sleep-related problems, but only sleep accommodations (e.g., let my child sleep with the lights on) were significant for father-reported sleep-related problems. Conclusion: Parents of children with elevated anxiety symptoms and sleep-related problems engage in accommodation related to their child's sleep (e.g., co-sleeping). Future research elucidating the potential bidirectional and causal links between parental accommodation and sleep-related problems is a necessary step in adapting sleep treatments for this population.